REPRESENTATION OF MENTORING RELATIONSHIPS AND STUDENTS’ PROFESSIONAL DEVELOPMENT IN TERMS OF TEACHING PRACTICE - Anužienė, Birutė; Šatienė, Salomėja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This article presents an analysis of the research aimed at students' attitude towards representation of mentoring relationships and an opportunity for their professional development in terms of teaching practice. The study is based on the assumption that the diversity of mentoring relationships and differences in their representation during teaching practice relate directly to the opportunities for students’ professional development. Mentoring is widely considered to be one of the models of support used in many different areas of society to meet the growing needs for personal and professional development. It is acknowledged that mentoring is a relationship between a more experienced, professional individual (a mentor) and a less experienced mentee. However, the following practical problem is identified: mentors themselves do not always recognise the variety of mentoring relationships or their impact on students’ professional development, i.e., opinions diverge when it comes to clarifying: What do mentoring relationships mean in terms of students' professional development? What explains the divergence of opinions or even the disagreement on the concept of mentoring relationships? How do different mentoring relationships affect students' professional development in terms of teaching practice? Searching for answers to the above problem questions provides new insights and possible practical solutions for analysing students' professional development during teaching practice. Thus, the goal of the study is to represent mentoring relationships and the professional development of students in terms of teaching practice. Research methods: analysis of scientific literature and questionnaire survey. Research results: the research shows that the multi-meaning of mentoring relationships depends on a context of an individual’s activity or a social field in which mentoring relationships take place. Research participants pointed out that mentoring relationships are understood by practice supervisors-mentors quite categorically, which restricts the professional development of students. During the research, it was found that mentoring relationships during students’ practical training should be expressed in different forms and practices to provide more opportunities for their professional development.